Investigating the Effect of Education Based on the Health Belief Model on Safe Behavior Preventing Children's Injuries in Mothers with under 5-Years Children - Sara Heidarikia; Marzieh Araban; Akbar Babaei Heydarabadi; Mahmood Latifi Seyed (Hamadan University of Medical Sciences, 2020)
Aims: Improving childrenchr('39')s health is one of the most important indicators of a communitychr('39')s health and preventing injuries in children requires safety. Therefore, the present study aimed to investigate the effect of theory-based education (Health Belief Model) on motherschr('39') safety behavior in preventing injuries from pediatric accidents. Materials & Methods: This semi-experimental study was conducted with 220 mothers with children under 5 years old. The data collection tool was a questionnaire based on knowledge, Health Belief Model constructs, behavior, and home safety checklist that was completed before and after educational intervention in both control and test groups by a Self-Report Method. The educational intervention based on the Health Belief Model was performed in 3 sessions using feedback speech, group discussion, clip display, and images. Data were analyzed by SPSS 22 statistical software and Mann-Whitney, Wilcoxon, t, and Chi-Square tests. Findings: The mean age and standard deviation of mothers were 28.50±5.20 years. There was a significant difference between the mean score of awareness, behavior, home safety and structural beliefs of the health belief model in the intervention group before and after the educational intervention (p<0.001) and in the control group between the mean score of perceived sensitivity and perceived barriers, behavior, home safety increased significantly. There was a significant difference in the score difference each of the variables before and after the intervention between the two groups. Conclusion: The educational program designed based on the Health Belief Model is effective in improving motherschr('39') beliefs and enhancing the safety behavior of mothers in preventing childrenchr('39')s accidents.